Comparative effectiveness of various treatment strategies for trigger finger by pairwise meta-analysis. (September 2020) - Shen, Po-Chih; Chou, Shih-Hsiang; Lu, Cheng-Chang; Fu, Yin-Chih; Lu, Chun-Kuan; Liu, Wen-Chih; Huang, Peng-Ju; Tien, Yin-Chun; Shih, Chia-Lung
Objective: To compare the efficacy of various strategies in the treatment of trigger finger. Data sources: A systematic literature search for randomized controlled trials to compare treatments for trigger finger was conducted through three online databases, Pubmed, Embase and Cochrane Library, from their inception dates to 22 May 2020. Methods: Relative risk (RR) with 95% confidence interval (CI) was used to evaluate the effect sizes in success rate for included articles. Results: Sixteen articles ( n = 1185) were included in our meta-analysis. The results showed that the efficacy of steroid injection was significantly better than the placebo group at short-term follow-ups (RR = 19.00, 95% CI = 1.17–309.77 for one-week; RR = 3.70, 95% CI = 3.70, 95% CI = 1.61–8.53 for one-month), and then became non-significant at four months (RR = 3.21, 95% CI = 0.88–11.79). There was no significant difference in success rate between steroid injection and nonsteroidal anti-inflammatory drug injection, and between open surgery and percutaneous release at all the follow-ups. Only surgical treatment had significantly better efficacy in success rate than steroid injection at all follow-ups (RR = 0.48, 95% CI = 0.34–0.66 for one-month; RR = 0.87, 95% CI = 0.80–0.96 for three-month; RR = 0.58, 95% CI = 0.48–0.68 for six-month; RR = 0.38, 95% CI = 0.20–0.72 for 12-month). Conclusion: There were no differences in efficacy between steroid injection and shockwave or nonsteroidal anti-inflammatory drug injection. The surgical treatments had the best efficacy among these treatments.